The structure of adverbs in bahdini kurdish and standard turkish language - Ali, Dilbreen (Humanities Journal of University of Zakho, 2022)
Adverbs have been thoroughly studied in grammar due to its immense significance. Throughout the use of adverbs, the speech utterance becomes evidently clear and more comprehensible. In this study, the term adverb will be investigated in terms of its use with the morphemes in both Kurdish and Turkish standard languages. As it is clear that both the Kurdish and Turkish languages go back to different language families. However, there are some shared common characteristics between them that could be investigated in their grammar. One of these topics is the forms of adverbs. The researcher uses descriptive as well as comparative method to analyze the topic understudy. The main aim and significance of this study lies within showing similarities and differences concerning the formation and structure of adverbs across the Kurdish language (Bahdini) and Standard Turkish language.